Pengaruh Materialitas Pendapatan, Biaya Dan Solvabilitas Terhadap Penerbitan Opini Going Concern Oleh Auditor Di Perusahaan Sektor Garment & Tekstil - Ricky Bryan D.P. Tampubolon; Angel gracia; Gladys Ananda; Nindie Olivianna (CV. ITTC INDONESIA, 2025)
This study examines the effect of revenue materiality, cost materiality, and solvency on the issuance of going concern audit opinions in garment and textile companies listed on the Indonesia Stock Exchange. A quantitative approach is employed using secondary data from financial statements and independent auditors’ reports. The dependent variable is the going concern audit opinion, measured using a dummy variable, while the independent variables include revenue materiality, cost materiality, and solvency, proxied by the Debt to Equity Ratio (DER). Binary logistic regression is used for data analysis. The results indicate that the regression model is valid, with a Nagelkerke R Square of 75.3% and a prediction accuracy of 93.3%. Partially, revenue materiality and cost materiality do not have a significant effect on going concern audit opinions. In contrast, solvency (DER) has a significant effect on the issuance of going concern opinions. These findings suggest that auditors emphasize long-term financial risk reflected in capital structure rather than operational account materiality when assessing going concern.